THE FORMATION OF PANCASILA STUDENT PROFILE IN STUDENT INDEPENDENT DIMENSIONS THROUGH PEER TUTOR IN PAI LEARNING - Abd. Muqit; Mir’atul Mukarromah; Amrullah Amrullah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
This study aimed to determine the design, implementation, and evaluation of the formation of Pancasila student profiles on the dimensions of student independence through peer tutors in PAI learning at SMPN 26 Surabaya. This research is a type of field research using a qualitative descriptive approach. The data collected is the result of observation, interviews, and documentation. The technique used in data analysis went through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study revealed that the design for the formation of a Pancasila student profile with the dimensions of student independence through peer tutoring in PAI learning was in the form of diagnostic assessments, forming groups and determining tutors, creating teaching modules. The implementation of the design for forming a Pancasila student profile shows that students study in groups which have been divided with the assistance of one tutor, one group contains 4-5 people, while the role of the teacher monitors and oversees the course of learning. Evaluation of the design of the formation of Pancasila student profiles in PAI learning is in the form of reflection, this activity is carried out after learning is complete. The benefit of this reflection activity is that a teacher will know about the strengths and weaknesses that exist.